2022
DOI: 10.1007/s00703-022-00907-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of linear multiple regression and artificial neural network for long-term rainfall forecasting in Western Australia

Abstract: Precipitation is one of the most intrinsic resources for manifold industrial activities all over Western Australia; consequently, immaculate rainfall prediction is indispensable for flood mitigation as well as water resources management. This study investigated the performance of artificial neural networks (ANN) and Linear multiple regression (LMR) analysis to forecast long-term seasonal spring rainfall in Western Australia, using lagged El Nino Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) as pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The findings indicated that these factors reasonably estimated the observed rainfall better than individual factors, implying that considering the synergistic effects of these influencing factors is important in interpreting and predicting the SON rainfall variations over SESA. Similar findings were presented by Rasel et al (2016), Khastagir et al (2022), Imteaz (2012), andWei et al (2023), but they focused on South, West, Victoria Australian rainfall and Arabian Peninsula rainfall, respectively. The authors demonstrated that rainfall predictability significantly enhanced based on the joint rainfall predictors relative to their separate Journal of Geophysical Research: Atmospheres 10.1029/2023JD040309 considerations.…”
Section: Conclusion and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The findings indicated that these factors reasonably estimated the observed rainfall better than individual factors, implying that considering the synergistic effects of these influencing factors is important in interpreting and predicting the SON rainfall variations over SESA. Similar findings were presented by Rasel et al (2016), Khastagir et al (2022), Imteaz (2012), andWei et al (2023), but they focused on South, West, Victoria Australian rainfall and Arabian Peninsula rainfall, respectively. The authors demonstrated that rainfall predictability significantly enhanced based on the joint rainfall predictors relative to their separate Journal of Geophysical Research: Atmospheres 10.1029/2023JD040309 considerations.…”
Section: Conclusion and Discussionsupporting
confidence: 81%
“…(2016), Khastagir et al. (2022), Mekanik and Imteaz (2012), and Wei et al. (2023), but they focused on South, West, Victoria Australian rainfall and Arabian Peninsula rainfall, respectively.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Some recently published works have applied and investigated how different ML algorithms and meteorological variables can contribute to precipitation forecasting in many regions worldwide, using various time scales according to the socioeconomic necessities of each region. Regarding the seasonal time scale, Khastagir et al (2022) evaluated the efficacy of predicting precipitation over Western Australia, which is indispensable for flood mitigation as well as water resource management for that region. The authors used ANN and multiple linear regression (MLR) analysis to forecast long-term seasonal spring precipitation using lagged El Niño-Southern Oscillation and Indian Ocean Dipole as potential climatic phenomena.…”
Section: ML Application In Rainfall Forecastingmentioning
confidence: 99%
“…In addition to climate change impacts on rainfall (and design rainfall), Australian rainfall is extremely manipulated by several climate drivers including El-Nino Southern Oscillation (ENSO), Indian Ocean Dipole (IOD), and Southern Annual Mode (SAM) [21][22][23][24]. Due to the natural variability and changes in the large-scale climatic modes from excessive greenhouse gas emissions, rainfall in the southeast area of Australia has decreased over the last 20 years [25].…”
Section: Introductionmentioning
confidence: 99%